Works published by USARB librarians in 2015 (Confluenţe Bibliologice, 2025)
The article highlights the works published by the Scientiﬁc Library USARB in 2015: bibliographies, catalogs, dictionaries. The works recorded achievements and professional performance today’s Library staﬀ with brief information about the time evolution of the Scientiﬁc Library USARB, inform about their activities within the Branch Libraries of Education in the North (LEN) ALRM and Librarianship Center in 2007-2015 period. The bibliographies published in Bibliographia Universitas collection is a pious homage to Bălţi superior institution which has celebrated 70 years of existence in 2015. Three of published works were awarded at the contest The Best Works in the Field of Library and Information Science in 2015.
Keywords: autographed book; university librarians; information and research activity